Position of sport in subjective quality of life of deaf people with different sport participation level - Nemček Dagmar; Mókušová Olympia (Sciendo, 2020)
The objective of the present study was to analyse the position of sport as a quality of the life domain (QOLD) in subjective quality of life (S-QOL) in deaf and hard of hearing (D/HH) people with different sport participation level. Three groups of D/HH people (n=164) were recruited for the study: elite and competitive athletes (ECA; n=30; mean age 22.2±1.8 years), recreational athletes (RA; n=22; mean age 25.2±2.0 years) and non-athletes (NA; n=112; mean age 26.8±1.9 years). D/HH ECA are the most satisfied in their lives equally with their sport participation, social relations, physical health and the level of independence together with general health. D/HH RA reported the highest satisfaction with sport participation, social relations and with physical health and the level of independence. Position of sport is in ECA and RA lives is the priority number one as well as the satisfaction with other QOLDs as social relations, physical health and level of independence. The position of sport participation in D/HH NA among the QOLDs was interestingly in the second place in the order together with physical health and level of independence domain. Inclusive participation in sport from the earliest age of D/HH children together with able-bodied peers should help better understand mutual communication. Than D/HH people would remain in regular sport participation in later life and so S-QOL among D/HH minority population would be significantly increased.